THE THE EFFECT OF USING LISTEN READ DISCUSS (LRD) STRATEGY ON STUDENTS READING COMPREHENSION OF DESCRIPTIVE TEXT ( A STUDY AT THE NINTH GRADE OF SMP NEGERI 2 ANGKOLA SELATAN IN 2020/2021 ACADEMIC YEAR) - Sophia Haryati Sirait (JURNAL LINER (Language Intelligence and Educational Research), 2020)
ABSTRACT Sirait, Sophia Haryati. 2020. The Effect of using Listen Read Discuss (LRD) strategy on Students’ Reading Coprehension of Descriptive text (A Study at the Ninth Grade Students of SMP Negeri 2 Angkola Selatan in 2020/2021 Academic Year) . A Skripsi, English Department Program. Institut Pendidikan Tapanuli Selatan (IPTS). The objective of this research is to know whether there is a significant effect of listen read discuss (LRD) strategy on students’ reading comprehension of descriptive text at the ninth grade students of SMP Negeri 2 Angkola Selatan in 2020/2021 Academic Year. This research uses experimental method with pre-experimental research design; one group pretest-posttest design. The population is all of the ninth grade students which consists of 123 students. Technique sampling that is used on this research is purposive sampling and the number of the samples are 32 students. In collecting the data, the researcher uses observation sheet to get the data of the application of listen read discuss (LRD) strategy and test to get the data of the students’ reading comprehension of descriptive text. The result of the application of listen read discuss (LRD) strategy was 3.58, it is categorized “very good”. The mean score of the students’ reading comprehension of descriptive text before using listen read discuss (LRD) strategy was 37, it is categorized “fail”. Meanwhile after using listen read discuss (LRD) strategy was 68.31, it is categorized “enough”. The researcher uses statistic process in analyzing the data by using ttest formula. Based on the data that had been analyzed, the result of data analyzing showed that ttest is higher than ttable (ttest 21.04> ttable 2.04). So, the hypothesis is accepted. It means that there is a significant effect of listen read discuss (LRD) strategy on students’ reading comprehension of descriptive text at the ninth grade students of SMP Negeri 2 Angkola Selatan in 2020/2021 Academic Year. Keyword: Listen Read Discuss strategy, Reading Descriptive text